Reluctant Teachers, Rustic Students And The Remoteness Of English - Mohamed, Abdul Rashid; Morad, Sabariah; Mohamed Ismail, Shaik Malik; Omar, Hamzah; Abdul Rahman, Wan Rose Eliza (Penerbit Universiti Sains Malaysia, 2006)
Initially this study started with the main objective of examining the English language environment available to the learners in a remote locality. However, when it was realized that there was no English language environment outside the English language classroom, the issue was approached from the perspective of the instructors and their instructions as they were the main source of English language exposure which the learners received. The main subjects of this study were a group of 25 pupils and three English language teachers in School A. Qualitative approach was used to gather data through observation, interviews and documents. Field and formal analysis were carried out using interpretative and descriptive statistics. In order to validate the findings, cross checking and triangulation were carried out. The study revealed that subjects received very minimal English language exposure. Whatever little exposure they received in class were of poor quality. The teacher was the only source of exposure through their English language class. As such, the English language teachers had a vital role to play. However, the "qualified" teachers were not motivated to teach. They treated School A as a temporary posting while awaiting a more permanent posting to a school or district of their choice. While they "buy" their time teaching was not very close to their heart. Thus, could these teachers motivate their students to learn? When they did teach they were hardly ever prepared and made numerous errors in English. Whatever little homework given was seldom returned by the students and if completed and handed in, the work was hardly looked at. In short the findings suggest that the reluctance of the English language teachers in the milieu of the rustic learners has resulted in the remoteness of English language in School A.